Pela estrada afora eu não vou bem sozinha: a experiência de mediação de leitura literária e a classificação dos livros de literatura infantil por faixa etária - Bruna Leite Galvao (2017)
Different studies have shown children's interest in literary works whose age group classification does not reflect their experiences with literary reading. This research aims at discussing the arbitrariness of the age group criteria associated with a concept of children and childhood thatoften does not correspond to the diversity of the students in Early childhood education. The particularities of the constitution of school groups have drawn attention to the presence of the teacher as a mediator of literary reading and the conditions under which the reading events happen. This research proposed to study a class of Early childhood education, with the fundamental presence of the teacher for the conduction of literary reading events, as well as to analyze the literary reading episodes carried out with children of that age so that they couldexperience the possibilities of interaction with works that we consider to be high-quality and suitable for a specific age group. The selection of the corpus was based on contemporary editorial production around the following questions: How does a group of three-year-old children carry out literary reading in a private school in Belo Horizonte? What kind ofinternalizations does the teacher mediation enable? The theoretical framework that underlies this research is based on the Psychology of Childhood, Language Studies, Sociology of Childhood and theoreticians responsible for studies on literary literacy, children's literature, as well as on children's experience with literature books. The contribution of this framework makes it possible to understand the child as a being of thought and action and to become aware of the affinity between childhood and literature, thus evidencing the need to offer a literary collection that meets childhood and does not trivialize or reduce its potentialities andparticularities. The methodological framework used addresses the assumptions of qualitative research. The initial analyzes of the data obtained from the field research, during which literary reading events were recorded in videos, showed that children are able to interpret the world in an active and creative fashion and, hence, the age group classification of childrens literature books favors an opposite movement, discrediting the children's capacity for interaction and sensemaking. That categorization ends up restricting the various interactions that children can establish with the literary works.